A High‐Performance Asymmetric Supercapacitor Based on Tungsten Oxide Nanoplates and Highly Reduced Graphene Oxide Electrodes. Issue 23 (17th March 2021) - Ashraf, Muhammad; Shah, Syed Shaheen; Khan, Ibrahim; Aziz, Md. Abdul; Ullah, Nisar; Khan, Mujeeb; Adil, Syed Farooq; Liaqat, Zainab; Usman, Muhammad; Tremel, Wolfgang; Tahir, Muhammad Nawaz
Abstract: Tungsten oxide/graphene hybrid materials are attractive semiconductors for energy‐related applications. Herein, we report an asymmetric supercapacitor (ASC, HRG//m‐WO3 ASC), fabricated from monoclinic tungsten oxide (m‐WO3 ) nanoplates as a negative electrode and highly reduced graphene oxide (HRG) as a positive electrode material. The supercapacitor performance of the prepared electrodes was evaluated in an aqueous electrolyte (1 m H2 SO4 ) using three‐ and two‐electrode systems. The HRG//m‐WO3 ASC exhibits a maximum specific capacitance of 389 F g −1 at a current density of 0.5 A g −1, with an associated high energy density of 93 Wh kg −1 at a power density of 500 W kg −1 in a wide 1.6 V operating potential window. In addition, the HRG//m‐WO3 ASC displays long‐term cycling stability, maintaining 92 % of the original specific capacitance after 5000 galvanostatic charge–discharge cycles. The m‐WO3 nanoplates were prepared hydrothermally while HRG was synthesized by a modified Hummers method. Abstract : Two dimensional nanomaterials : An asymmetric supercapacitor (ASC, HRG//m‐WO3 ASC) fabricated from tungsten oxide (m‐WO3 ) nanoplates as a negative electrode and highly reduced graphene oxide (HRG) as a positive electrode material attains specific capacitance of 389 F g −1 at a current density of 0.5 A g −1, with an associated high energy density of 93 Wh kg −1 at a power density of 500 W kg −1 in a wide 1.6 V operating potential window. In addition, the HRG//m‐WO3 ASC displays long‐term cycling‐stability, maintaining around 92 % of the original specific capacitance after 5000 galvanostatic charge–discharge cycles.